Applied economic evaluation of nutritional support units (2014)
In the health sector, the interest for making analyzes on economic technology assessment in health led to international and national guidelines to develop different economic evaluation and instructions for incorporating economic evaluation in clinical practice guidelines level in order to make decisions in terms of costs and consequences. In this article, the importance of nutritional care (including the use of tools of economic evaluation conducted as part of the process units of nutritional support in order to facilitate clinical outcomes) will debate and compare benefits and costs of nutritional care in hospitals. The main function of the nutritional support units is to improve and maintain the health status of the patient through comprehensive nutritional care, but in a normative way, when such care requires additional or pharmacological alternatives, hospitals must provide treatment to lowest cost and maximum benefit to the patient. Effectiveness, cost analysis-utility and cost analysis from the administration of nutritional support units, limitations and challenges posed to include analysis used in economic evaluation to understand, cost reduction, cost analysis face-benefit, lead to motivate research and training of health professionals on the assessment of the economic costs and benefits of nutritional therapy. © 2014 Universidad Nacional de Colombia. All rights reserved.